Resident Management System for Private Residential - Othman, Muhaini; Ahmad Nizar, Nur Sobah (Applied Information Technology And Computer Science, 2020)
Resident Management System for Private Residential is a system developed to effectively operates the management of residents in Bistari Hostel. The goal was to develop a web-based system which can be accessible by an administrator, fellow residents including public students who wishes to rent a room at Bistari Hostel. The problem arise from the current system was student may not be able to meet the operational time allocated due to class’s schedule. Due to on-shelves manual record using physical form, the processing time for resident’s registration may take longer as management staff were unaware of room’s availability. Whereas forms’ redundancy may happen due to unrestricted amount of forms submitted by each potential and existing resident. Hence, it maximizes the management’s workload, and affected the flexibility of resident’s information. This system was developed using Waterfall model of structured approach. A management staff who will act as an administrator will be able to manage the records of existing residents including monthly rental payment and request forms submitted. Whereas residents will be able to submit rent payment verification and maintenance request forms, including the accessibility to view monthly rent statement. Whereas public students will have access to a request for accommodation form and be able to view the submitted form’s status. Through the pro-posed system, workload of management staff can be reduced since the system will systematically conquest the manual process of acquiring resident applications and rent payment verification and maintenance requests from every potential and existing residents of Bistari Hostel.